2017
DOI: 10.1002/chem.201700139
|View full text |Cite
|
Sign up to set email alerts
|

Robust MOFs of “tsg” Topology Based on Trigonal Prismatic Organic and Metal Cluster SBUs: Single Crystal to Single Crystal Postsynthetic Metal Exchange and Selective CO2 Capture

Abstract: The self-assembly of a rigid and trigonal prismatic triptycene-hexaacid H THA with Co(NO ) or Mn(NO ) leads to isostructural metal-organic frameworks (MOFs) that are sustained by 6-connecting metal cluster [M (μ -O)(COO) ] secondary building units (SBUs). The Co- and Mn-MOFs, constructed from organic and metal-cluster building blocks that are both trigonal prismatic, correspond to the heretofore unknown "tsg" topology. Due to the rigidity and concave attributes of H THA, the networks in the Co- and Mn-MOFs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…All three Co(II) ions were found to exhibit distorted octahedral geometry and were involved in the formation of a unique {Co 3 (m 3 -OH)(COO) 6 } trigonal prismatic secondary building unit (SBU) that acts as a building block in the construction of the overall 3D framework. [57][58][59] These three Co(II) centers resulted in the formation of a scalene triangle (Co/Co: 3.405, 3.459, 3.721Å) where the centre of the triangle is being occupied by a bridging OH group (m 3 -OH) that connects the three Co(II) ions (Co-O: 2.035, 2.050, 2.055Å). Each trigonal prismatic SBU is linked to six carboxylate ligands (ve in chelating mode and one in a monodentate fashion) and hence acts as a 6-connected node.…”
Section: Resultsmentioning
confidence: 99%
“…All three Co(II) ions were found to exhibit distorted octahedral geometry and were involved in the formation of a unique {Co 3 (m 3 -OH)(COO) 6 } trigonal prismatic secondary building unit (SBU) that acts as a building block in the construction of the overall 3D framework. [57][58][59] These three Co(II) centers resulted in the formation of a scalene triangle (Co/Co: 3.405, 3.459, 3.721Å) where the centre of the triangle is being occupied by a bridging OH group (m 3 -OH) that connects the three Co(II) ions (Co-O: 2.035, 2.050, 2.055Å). Each trigonal prismatic SBU is linked to six carboxylate ligands (ve in chelating mode and one in a monodentate fashion) and hence acts as a 6-connected node.…”
Section: Resultsmentioning
confidence: 99%
“…Co, C, N and O are represented by purple, gray, blue and red, respectively, and H atoms and solvent molecules are omitted for clarity. 150 The acs net with transitivity [1122] is the sole possible edge-transitive net ("default net") constructed from a trigonal prism SBU. Early examples included the MIL-88 series or MOF-235, constructed from the metal trinuclear clusters and linear linkers.…”
Section: Mofs Based On Acs and Acs-derived Netsmentioning
confidence: 99%
“…99,152 The Co-THA MOF has been recently reported via the combination of the rigid triptycene-hexacarboxylate ligands and the cobalt trinuclear clusters (Figure . 14). 150 The high degree of rigidity imparted by the triptycene core in the hexacarboxylate linker led to the entire geometry of the ligands to remain unchanged during the MOF synthesis. Thus, this branched linker can be viewed as a trigonal prismatic MBB, and when combined with the metal trinuclear clusters, led to the generation of a MOF example based on the acs-derived tsg net.…”
Section: Mofs Based On Acs and Acs-derived Netsmentioning
confidence: 99%
“…The H 2 uptake by TBPALs was found to be in the range of 11.4-16.2 mg/g ( Table 2 and Figure 6). The highest value was obtained for TBPAL2 (16.2 mg/g), and this is better than various MOPs and MOFs such as azo-bridged porphyrin-based conjugated microporous polymers (8.6-11.5 mg/g) (Xu et al, 2016b), triptycene-based hexakis (metalsalphens) (6-7 mg/g) (Reinhard et al, 2018), 3D ultramicroporous triptycene-based polyimide framework (14.1 mg/g) (Ghanem et al, 2016), rigid triptycene-hexaacid H 6 THA (7.8-11.8 mg/g) (Chandrasekhar et al, 2017a), porous hydrogenbonded MOFs (1.1-1.3 mg/g) (Chandrasekhar et al, 2017b), carbazole-based POPs (11.9-12.9 mg/g) (Zhu et al, 2014), and phthalocyanine-based porous polymer (9 mg/g). (Neti et al, 2015) From the above comparison, it is clear that TBPALs reported herein show H 2 uptake abilities that are better than several microporous polymeric networks reported previously in the literature.…”
Section: Resultsmentioning
confidence: 96%